2009
DOI: 10.1177/1066480708328565
|View full text |Cite
|
Sign up to set email alerts
|

Counseling African American Women: Let's Talk About Sex!

Abstract: In the absence of clear, specific literature, this article provides information about the sexuality of African American women and identifies culturally relevant practices counselors may use to gain understanding of and respond to sex-related issues (i.e., development, identity, and activity) of African American women. Implications for counselors and recommendations for broaching sexual matters are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…As suggested in previous studies, many of the messages communicated by paternal caregivers in the present study focused on imparting their values and attitudes regarding sexual relationships and women's sexual practices as opposed to sexual education and information (DiIorio et al 1999;Hutchinson and Cederbaum 2011). Some of the messages received by participants in the present study indicated that remaining chaste until marriage was the only appropriate option for women (Thomas, Crook, and Cobia 2009;Wyatt 1997). Additionally, across some of the messages, paternal caregivers appeared to express attitudes regarding men's sexual practices as well.…”
Section: Sex Education 249mentioning
confidence: 73%
See 4 more Smart Citations
“…As suggested in previous studies, many of the messages communicated by paternal caregivers in the present study focused on imparting their values and attitudes regarding sexual relationships and women's sexual practices as opposed to sexual education and information (DiIorio et al 1999;Hutchinson and Cederbaum 2011). Some of the messages received by participants in the present study indicated that remaining chaste until marriage was the only appropriate option for women (Thomas, Crook, and Cobia 2009;Wyatt 1997). Additionally, across some of the messages, paternal caregivers appeared to express attitudes regarding men's sexual practices as well.…”
Section: Sex Education 249mentioning
confidence: 73%
“…Previous studies have noted that, as children and young people, African-American women may receive messages that consistently imply that their sexuality should be suppressed and they should remain chaste (Thomas, Crook, and Cobia 2009;Jackson and Greene 2000;Wyatt 1997). However, much of this research has focused on the receipt of these messages from mothers, grandmothers and other African-American women in their communities.…”
Section: Present Studymentioning
confidence: 96%
See 3 more Smart Citations